Antioxidant and Nephroprotective Potential of Aegle marmelos Leaves Extract. Issue 4 (2nd October 2017) - Dwivedi, Jaya; Singh, Manvendra; Sharma, Swapnil; Sharma, Sharad
ABSTRACT: The nephroprotective activity of hydro-alcoholic (HAEAM) and ethyl acetate (EAEAM) extracts of Aegle marmelos leaves were evaluated against nephrotoxicity induced by cisplatin (CP), a widely used chemotherapeutic agent in cancer therapy. Wistar rats were treated with CP (6 mg.kg – 1 ; i.p.). Treatment groups received the same dose of CP, along with HAEAM and EAEAM (200 and 400 mg.kg –1 ) orally for 5 d. Blood urea nitrogen (BUN), serum creatinine, and antioxidant enzymes were estimated in renal tissues. EAEAM exhibited minimum IC50 values 6.13 ± 1.05, 67.34 ± 1.7, 59.7 ± 3.9, and 49.17 ± 2.19 μ g.mL – 1 . EAEAM (400 mg.kg – 1 ) decreased the creatinine levels from 2.29 ± 0.387 to 0.96 ± 0.095 mg.dL – 1 and BUN from 92.06 ± 7.949 to 38.18 ± 5.686 mg.dL – 1 and restored the activities of renal antioxidant enzymes, decreased the lipid peroxidasde (LPO) levels from 158.70 ± 3.542 to 106.91 ± 5.876 nM.g – 1, and increased superoxide dismutase (SOD) levels from 12.59 ± 0.463 to 29.95 ± 5.222 U.g – 1, glutathione (GSH) from 0.24 ± 0.029 to 0.57 ± 0.048 μ M.g – 1, and catalase (CAT) from 1.14 ± 0.067 to 3.27 ± 0.296 U.mg – 1 ).